2004
DOI: 10.1093/jxb/erh143
|View full text |Cite
|
Sign up to set email alerts
|

Responses of primary and secondary metabolism to sugar accumulation revealed by microarray expression analysis of the Arabidopsis mutant, pho3

Abstract: The Arabidopsis mutant pho3 accumulates sucrose and other carbohydrates to high levels, providing a means of investigating the genomic response to sucrose accumulation using microarray analysis. Wild-type and mutant plants were grown in soil to the mature rosette stage for the analysis of gene expression using the Affymetrix ATH1 chip, containing more than 22,500 probe sets. Small, but significant, decreases were observed in the expression of many genes encoding enzymes and regulatory proteins involved in prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
179
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(193 citation statements)
references
References 50 publications
10
179
1
3
Order By: Relevance
“…In contrast, the APase activity on the root surface is largely reduced in the suc2-5 mutant. The high accumulation of anthocyanin and starch in shoots, and the reduced production of APase in roots, were also observed in pho3, another mutant allele of the SUC2 gene (Zakhleniuk et al, 2001;Lloyd and Zakhleniuk, 2004). Taken together, these results show that the hps1 mutant has enhanced sensitivity in multiple plant responses to Pi starvation, and this is primarily due to increased levels of Suc, which acts as a global regulator of plant responses to Pi starvation.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In contrast, the APase activity on the root surface is largely reduced in the suc2-5 mutant. The high accumulation of anthocyanin and starch in shoots, and the reduced production of APase in roots, were also observed in pho3, another mutant allele of the SUC2 gene (Zakhleniuk et al, 2001;Lloyd and Zakhleniuk, 2004). Taken together, these results show that the hps1 mutant has enhanced sensitivity in multiple plant responses to Pi starvation, and this is primarily due to increased levels of Suc, which acts as a global regulator of plant responses to Pi starvation.…”
Section: Discussionmentioning
confidence: 58%
“…The similar effects of photosynthates on Pi starvation-induced cluster root formation in white lupin and the expression of miRNA399 in common bean (Phaseolus vulgaris) have also been observed (Zhou et al, 2008;Liu et al, 2010b). In contrast, the Arabidopsis pho3 mutant carries a defective copy of the SUCROSE TRANSPORTER2 (SUC2) gene, leading to substantially reduced transport of Suc from shoot to root and the suppression of induction and secretion of APase on its root surface (Zakhleniuk et al, 2001;Lloyd and Zakhleniuk, 2004). In addition, earlier studies have revealed that the expression of many genes involved in the synthesis, translocation, and degradation of Suc was altered during Pi starvation (Hammond et al, 2003;Vance et al, 2003;Wu et al, 2003;Misson et al, 2005;MĂŒ ller et al, 2007).…”
mentioning
confidence: 80%
“…There is growing evidence that long-distance Suc transport plays an important role in phosphorous responses (Liu et al, 2005;Karthikeyan et al, 2007;White, 2008, 2011). The pho3 mutation, which was identified in a screen for reduced acid phosphatase activity during P limitations, turned out to be a mutant allele of AtSUC2 (Lloyd and Zakhleniuk, 2004). Both a reduction in photosynthesis and stem girdling, which blocks phloem transport, attenuate P deficiency responses in roots, including a decrease in the expression of many PSI genes (Liu et al, 2005;Karthikeyan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In wild‐type plants, GPT2 expression is induced in imbibed seeds (Finch‐Savage et al . 2007), in response to exogenous and endogenous increases in sucrose (Lloyd & Zakhleniuk 2004; Gonzali et al . 2006), in response to an increase in light intensity (Athanasiou et al .…”
Section: Introductionmentioning
confidence: 99%